Avoiding sovereign default contagion: A normative analysis - De Ferra, S; Mallucci, E (Elsevier, 2024)
Should debtor countries support each other during sovereign debt crises? We answer this question through the lens of a two-country sovereign-default model that we calibrate to the euro-area periphery. First, we look at cross-country bailouts. We find that whenever agents anticipate them, bailouts induce higher borrowings, and yet still enhance welfare. Second, we look at the borrowing choices of a global central borrower. We find that central borrower’s policies reduce debt and improve the joint welfare of the two countries. Yet, welfare gains are uneven. In our baseline specification, one of the two countries sees a decline of welfare under the planner’s rules. We conclude that central planner policies may be politically unfeasible.